A study on obesity and cardiovascular risk factors among male soldiers in Melaka, Malaysia - Daud, Norwati (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
The prevalence of obesity among army personnel is increasing in many countries. Therefore, this study was aimed to determine the prevalence of obesity and to estimate the 10-year Framingham risk of coronary heart disease event among male army personnel in Malaysia. A cross sectional study was performed on 392 male army personnel between January and July 2008. Their BMI was calculated and the parameters for calculation of the 10-year Framingham risk were measured. Data was analyzed using SPSS version 16.0. The results showed that the prevalence of obesity was 15.6% (95% CI: 12.01, 19.20). Majority of the respondents (95.9%) had low risk of coronary heart disease event in next 10 years. This study indicates that the prevalence of • obesity among male soldiers in Malaysia was higher than that of the Malaysian general population based on the National Health and Morbidity Survey (NHMS) III 2006. However, majority of them had low risk of coronary heart disease.